Digital Agro Advisory for Smallholders - Tesfaye, Kindie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation to Extension and Crop Development Directorates Ministry of Agriculture. Adama, Ethiopia. April 11-13, 2022.